2010
DOI: 10.2135/cropsci2008.12.0741
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles of Orchardgrass, Tall Fescue, Perennial Ryegrass, and Alfalfa

Abstract: Recent research shows that the meat from beef animals finished on pasture has greater concentrations of omega‐3 fatty acid (FA) and conjugated linoleic acids (CLA) compared with animals finished on high‐concentrate diets. However, little is known about the FA concentrations in forage that might alter these FA in the meat of pasture‐finished beef. The objective was to determine the FA variation between and within forage species commonly grown in pastures in the Midwest. A secondary objective was to identify phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
7
22
0
Order By: Relevance
“…In fact, CP content is positively correlated with total FA content (R 2 = 0.78; P < 0.001 data not shown), and with total UFA content (R 2 = 0.75; P < 0.01) ( Figure 3) probably as result of the higher efficiency of lipid synthesis in the leaves than in stems, as reported by Mayland et al (1976). In fact a positive relationship has been found between chlorophyll and total FA, included PUFA in plant (Dierking et al 2010), and it is probable that chlorophyll will be an important criterion in plant breeding for manipulation of FA levels. A negative relationship was observed between WSC and EE (R 2 = À0.47, P < 0.01; data not shown) in agreement with Cabiddu et al (2000), Witkowska et al (2008) and Gregorini et al (2008), probably because during plant lipid metabolism some of the carbohydrate pool, generated by the photosynthetic cycle, is complexed with FA to produce polar lipids, in particular phospholipids and glycolipids (Hawke 1973).…”
Section: Fatty Acidsmentioning
confidence: 57%
See 1 more Smart Citation
“…In fact, CP content is positively correlated with total FA content (R 2 = 0.78; P < 0.001 data not shown), and with total UFA content (R 2 = 0.75; P < 0.01) ( Figure 3) probably as result of the higher efficiency of lipid synthesis in the leaves than in stems, as reported by Mayland et al (1976). In fact a positive relationship has been found between chlorophyll and total FA, included PUFA in plant (Dierking et al 2010), and it is probable that chlorophyll will be an important criterion in plant breeding for manipulation of FA levels. A negative relationship was observed between WSC and EE (R 2 = À0.47, P < 0.01; data not shown) in agreement with Cabiddu et al (2000), Witkowska et al (2008) and Gregorini et al (2008), probably because during plant lipid metabolism some of the carbohydrate pool, generated by the photosynthetic cycle, is complexed with FA to produce polar lipids, in particular phospholipids and glycolipids (Hawke 1973).…”
Section: Fatty Acidsmentioning
confidence: 57%
“…In fact a positive relationship has been found between chlorophyll and total FA, included PUFA in plant (Dierking et al . ), and it is probable that chlorophyll will be an important criterion in plant breeding for manipulation of FA levels. A negative relationship was observed between WSC and EE ( R 2 = −0.47, P < 0.01; data not shown) in agreement with Cabiddu et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Boufaied et al (2003a) observed a higher content of linoleic, ALA and total fatty acids in cocksfoot (Dactylis glomerata) and timothy (Phleum pratense) in summer regrowth than in spring cut. Similarly, reported a higher concentration of ALA in cocksfoot, timothy and red clover (Trifolium pra-tense) in summer regrowth, while there were Dierking et al (2010) comparable levels in lucerne (Medicago sativa) from both cuts. A progressive increase in total FAs and in the proportion of ALA was observed in the stay-green trait of perennial ryegrass (Lolium perenne) from early to late season (Dewhurst et al, 2002).…”
Section: Fresh Foragesmentioning
confidence: 90%
“…The different covariance structures of repeated matrices for FA content in stover (model 1) and ears (model 2) were evaluated according to Littell et al 24 and Wang and Goonewardene25 using the Akaike information criterion and the Schwarz Bayesian criterion. A heterogeneous compound symmetry was the best fit for model 1, while ANTE26 was the best fit for model 2.…”
Section: Methodsmentioning
confidence: 97%